2015
DOI: 10.1165/rcmb.2014-0329oc
|View full text |Cite
|
Sign up to set email alerts
|

The Alteration of Neonatal Raphe Neurons by Prenatal–Perinatal Nicotine. Meaning for Sudden Infant Death Syndrome

Abstract: Nicotine may link maternal cigarette smoking with respiratory dysfunctions in sudden infant death syndrome (SIDS). Prenatal-perinatal nicotine exposure blunts ventilatory responses to hypercapnia and reduces central respiratory chemoreception in mouse neonates at Postnatal Days 0 (P0) to P3. This suggests that raphe neurons, which are altered in SIDS and contribute to central respiratory chemoreception, may be affected by nicotine. We therefore investigated whether prenatal-perinatal nicotine exposure affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 49 publications
(68 reference statements)
1
23
0
2
Order By: Relevance
“…Cerpa et al . () recently further showed that the increased 5‐HT 1A R expression in raphe 5‐HT neurons is accompanied by reduced spontaneous firing frequency and reduced hypercapnia activated c‐ Fos ‐positive 5‐HT neuron numbers in the raphe obscurus of P3–5 mice. Taken together, results of these studies suggest that perinatal nicotine exposure can lead to a dysfunctional 5‐HT system in the neonate offspring, and the phenotypes observed in our current study may reflect the results of the combination of nicotine exposure and 5‐HT deficiency.…”
Section: Discussionmentioning
confidence: 88%
“…Cerpa et al . () recently further showed that the increased 5‐HT 1A R expression in raphe 5‐HT neurons is accompanied by reduced spontaneous firing frequency and reduced hypercapnia activated c‐ Fos ‐positive 5‐HT neuron numbers in the raphe obscurus of P3–5 mice. Taken together, results of these studies suggest that perinatal nicotine exposure can lead to a dysfunctional 5‐HT system in the neonate offspring, and the phenotypes observed in our current study may reflect the results of the combination of nicotine exposure and 5‐HT deficiency.…”
Section: Discussionmentioning
confidence: 88%
“…Shatet al 17 estimou que 20,7% dos casos de SMSI poderiam ser prevenidos se mães não fumassem durante gravidez. Estudos apontam que o tabagismo é um potente fator de risco para SMSI 10,18 , mas também um dos que mais facilmente pode ser evitado, fato que reitera importância de políticas públicas anti-tabagismo especialmente durante gestação. Em nosso estudo, encontramos que 29 (78%) das mães eram tabagistas.…”
Section: Discussionunclassified
“…Lei et al (2015) report that, in medullary slices sampled from prenatally exposed rats, responses to acidification (increased burst frequency and reduced integrated amplitude) are lower than in controls, indicating a blunting effect on central chemoreception. In mouse, prenatal to early postnatal nicotine exposure also causes specific changes in the raphe obscurus nucleus (decreased number of serotoninergic neurons and increased expression of 5-HT 1A autoreceptors) (Cerpa et al 2015).…”
Section: Intrinsic and Extrinsic Risk Factorsmentioning
confidence: 99%
“…In mouse, prenatal to early postnatal nicotine exposure also causes specific changes in the raphe obscurus nucleus (decreased number of serotoninergic neurons and increased expression of 5‐HT 1A autoreceptors) (Cerpa et al . ).…”
Section: Introductionmentioning
confidence: 97%